Antennae-abundant expression of candidate cytochrome P450 genes associated with odorant degradation in the asian citrus psyllid, Diaphorina citri - Kuang, Yinhui; Xiong, Yu; Chen, Xue Dong; Yu, Xiudao (Frontiers in Physiology, 2022)
The Asian citrus psyllid, Diaphorina citri, is a notorious pest that is an efficient vector for Candidatus Liberibacter asiaticus (CLas), the causal agent of citrus huanglongbing (HLB). The olfactory system of insects is crucial for foraging and mating behavior. Antennae-abundant odorant degrading enzymes (ODEs), including cytochrome P450 (CYPs), are important in degrading redundant odorant molecules to recover the insect olfactory. In this study, to isolate the antennal CYP genes of D. citri, we generated four transcriptomes from female/male antennae and body through deep sequencing of RNA libraries. Seven DcCYP genes preferentially expressed in antennae were first identified by comparing the antennal and body transcriptomes. Phylogenetic analysis grouped four DcCYPs (DcCYP6a13, DcCYP6j1, DcCYP6k1, and DcCYP6a2) into the CYP3 class, whereas DcCYP4d2, DcCYP4c62, and DcCYP4d8 were clustered in the CYP4 clade. qRT-PCR analyses across developmental stages and tissues showed they were antennae-abundant in both genders and constantly expressed from the first instar nymph to the adult. The results presented here highlight the isolation and expression of CYP genes in D. citri antennae, providing valuable insights into their putative role in odorant degradation.